Construction of MoS2/NiFe-Ni foam p-n heterojunction as photoanode for tetracycline degradation and simultaneous cathodic hydrogen evolution. Issue 5 (October 2022) - Yu, Jiuheng; Cong, Sumin; Liu, Baojun; Teng, Wei
Abstract: In this work, simultaneously removing antibiotic tetracycline (TC) from wastewater coupled with pure H2 generation has been successfully achieved through photoelectrocatalytic (PEC) technique by using MoS2 /NiFe-Ni foam photoanode. The MoS2 /NiFe-Ni foam was synthesized by a simple hydrothermal and electrodeposition method. The designed bifunctional PEC system leads to a high degradation efficiency of dissolved TC by up to 92% during 100 min reaction time under visible light irradiation. Meanwhile, the hydrogen production at the cathode was as high as 61.46 μmol cm -2, which was 15 times higher than that when the NiFe-Ni foam was used as a photoanode. The enhanced photoelectrocatalytic activity is attributed to the construction of the type-II p-n heterojunction between MoS2 and NiFe-LDH. Which contributes to improve the separation and migration efficiency of photogenerated charges. This study provides a new method for the preparation of efficient type-II p-n heterojunction catalysts. Highlights: MoS2 /NiFe-Ni foam was synthesized by simple electrodeposition and hydrothermal methods. The construction of type II p-n heterojunctions improved the degradation efficiency of TC effectively. A possible mechanism for the TC degradation by MoS2 /NiFe-Ni foam and simultaneous hydrogen evolution at cathode was proposed.